Que sont les normes pour les psychanalystes? Y a-t-il des limites pour la transformation du corps? - Porchat, Patricia [UNESP] (CAIRN, 2017)
Body transformations in relation with gender identity increase every day, and raise the question about whether one is to follow individual or collective norms. What guides our listening and interventions with patients that are submitted to different, even non-gender-related, body modifications. We suggest that psychoanalysts shall stand outside norms. In order to do so, they should develop a condition of supportability that will only be achieved when they are faced to their own prejudice. Through a fragment of a clinic case we approach the limits the analyst identified in her own self as she was faced to the body changes of her patient. Afterwards, we raise some possible contemporary meanings of the various forms of body modification, and consider the fact that the body changes and transforms itself despite norms and despite ourselves. We remind Judith Butler's conception of gender understood as a norm which creates intelligibility. Finally, we note that to follow social, gender and body transformations, the analyst should stand outside norms and live as if no strangeness were ever strange to her.
What are norms for psychoanalysts? Are there limits to the transformation of the body?
Keywords: Body; Body changes; Gender; Judith Butler; Mask; Norms; Psychoanalysis; Supportability